Preparation method of nano rubber toughened double amidoxime-based hydrogel uranium adsorbent

By introducing nanorubber and digasmidoxime groups into polyacrylamide, the hydrogel uranium adsorbent for nanorubber toughening is solved, and the problems of polyacrylamide are brittle and insufficient adsorption performance are achieved, and high-efficiency uranyl is achieved Ion adsorption and mechanical properties are improved.

CN119258933APending Publication Date: 2025-01-07TECHN PHYSICS INST HEILONGJIANG ACADOF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411636154.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Polyacrylamide is fragile after water absorption and swelling, and lacks chelated uranium groups on the surface, which affects its application in the field of uranium adsorption.

Method used

By combining radiation and chemical grafting, polyacrylamide is toughened by nanorubber, diacrylamide group is introduced to form nanorubber toughened diacrylamide oxime hydrogel uranium adsorbent, which is improved. Mechanical properties and chelation of uranyl ions.

Benefits of technology

It significantly improves the adsorption performance, enhances the mechanical properties of the material and the adsorption ability of uranyl ions, and is suitable for repeated adsorption and desorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258933A_ABST
    Figure CN119258933A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a nano rubber toughened double amidoxime-based hydrogel uranium adsorbent, in particular to a preparation method of a nano rubber toughened double amidoxime-based hydrogel uranium adsorbent. The invention aims to solve the problems that polyacrylamide has poor mechanical properties such as fragility and insufficient toughness after absorbing water and swelling, lacks uranium chelated groups on the surface, and is not beneficial to repeated adsorption and desorption use in the practical application process. The method comprises the following steps: uniformly dispersing nano rubber in polyacrylamide by utilizing an irradiation method to prepare a polyacrylamide / nano rubber hydrogel matrix; chemically soaking and grafting a DAMN group to obtain a hydrogel precursor material containing a cyano group; through an amidoximation reaction, the conversion from a cyano group to an oximido group is realized, and the hydrogel containing double amidoxime groups is obtained. According to the invention, the double amidoxime-based hydrogel uranium adsorption material with high mechanical property, high adsorption property and good adsorption selectivity is prepared. The prepared adsorbent is used for uranium adsorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a nano rubber toughened bisamidoximine-based hydrogel uranium adsorbent, and specifically belongs to the field of uranium-containing radioactive wastewater treatment. Background Art

[0002] With the continuous growth of global energy demand, nuclear energy, as a clean and efficient form of energy, has become increasingly important. As a key raw material for nuclear power generation, the recovery and reuse of uranium is not only related to the sustainable development of nuclear energy, but also an important part of ensuring energy security. However, the extraction and purification process of uranium is complicated and costly, and its potential impact on the environment and human body cannot be ignored. Common uranium extraction and purification methods mainly use adsorption, chemical deposition, ion exchange, solvent extraction, membrane separation and biological methods. Among them, the adsorption method has the advantages of simple operation, strong targeting and wide source of materials. Among the different physical and chemical interactions, chelation in adsorption is an important mechanism for the directional adsorption of target pollutants. At the same time, the construction of nucleophilic ligand chelation is an effective method for selective adsorption.

[0003] The amidoxime group (AO) is a good nucleophilic ligand for adsorbing uranium. Therefore, the structural properties of the material and its adsorption to uranyl can be further improved by introducing amidoxime functional groups through appropriate physical and chemical modifications to directionally identify, capture or fix uranyl ions in different forms. Diaminomaleonitrile (DAMN) has both amino (NH2) and cyano (C≡N) groups, which are used as precursors of AO ligands. Through amidoximation reactions, dual AO functional groups can be generated, which can be better used to recover uranium from aqueous solutions.

[0004] Polyacrylamide (PAM) has good hydrophilicity, and its surface has active groups such as amide groups that are easy to functionalize and modify. In addition, it presents a three-dimensional porous, high specific surface area and long-life hydrogel state in the water system. The gel retains a large amount of water, and uranyl ions can easily enter, which is beneficial to the improvement of the adsorption performance of the material. However, after PAM absorbs water and swells, it will show problems of poor mechanical properties such as fragility and insufficient toughness, which is not conducive to repeated adsorption and desorption in practical applications. At the same time, the surface of the pure PAM hydrogel matrix lacks uranium chelating groups. These problems have seriously affected its application in the field of uranium adsorption. Summary of the invention

[0005] The invention provides a method for preparing a nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent in order to solve the problem that polyacrylamide has poor mechanical properties such as fragility and insufficient toughness after absorbing water and swelling, lacks uranium chelating groups on the surface, and is not conducive to repeated adsorption and desorption in practical applications.

[0006] The nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent is prepared by combining irradiation with chemical grafting, using acrylamide (AM) as a grafting matrix and nano-rubber (PB) as a toughening and strengthening unit, and grafting DAMN groups through multiple steps of organic solution soaking and amidoximation reaction.

[0007] A method for preparing a nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent is specifically carried out according to the following steps:

[0008] 1. Stir the polybutadiene nano rubber latex and acrylamide in a colorimetric tube to obtain a mixed system; then irradiate with a dose of 2.5 kGy to 20 kGy. 60 Co-γ-ray irradiation for 0.5 h to 4 h, the product was fully swollen after washing to obtain polyacrylamide / nano rubber hydrogel PAM / PB;

[0009] 2. Soak the polyacrylamide / nano rubber hydrogel PAM / PB obtained in step 1 in a sodium hypochlorite solution, then wash to remove residual sodium hypochlorite, then soak in a sodium thiosulfate solution, then wash and dry to obtain an amino-substituted product hydrogel PAM / PB-NH2;

[0010] 3. Soaking the hydrogel PAM / PB-NH2 obtained in step 2 in a glutaraldehyde solution, then washing and drying to obtain an aldehyde-substituted product hydrogel PAM / PB-CHO;

[0011] 4. Soaking the hydrogel PAM / PB-CHO obtained in step 3 in a diaminomaleonitrile solution, then washing and drying to obtain a DAMN-grafted product hydrogel PAM / PB-DAMN;

[0012] 5. Dissolve hydroxylamine hydrochloride in a methanol / water mixed solution, adjust the pH, add the hydrogel PAM / PB-DAMN obtained in step 4 to obtain a reaction system, heat the reaction system for reaction, cool it to room temperature, wash and dry it, and obtain a nano-rubber toughened diamidoximine-based hydrogel uranium adsorbent PAM / PB-DAMN-AO.

[0013] The beneficial effects of the present invention are:

[0014] The present invention utilizes irradiation to uniformly disperse PB in PAM, and PB, as a toughening and strengthening unit, has an improving effect on the mechanical properties of PAM. At the same time, after multi-step chemical soaking and grafting of DAMN groups and amidoximation reaction, a nano-rubber toughened bisamidoxime-based hydrogel uranium adsorbent is obtained. The presence of the bifunctional group improves the chelation effect on uranyl ions and significantly improves the adsorption performance.

[0015] The nano rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared by the invention is used for uranium adsorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the FT-IR image of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1;

[0017] Figure 2 is a SEM image of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1;

[0018] Figure 3 The XPS graphs of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1; wherein (a) is the XPS total spectrum, (b) is the C1s high-resolution spectrum, (c) is the N 1s high-resolution spectrum, and (d) is the O1s high-resolution spectrum;

[0019] Figure 4 1 is a BET diagram of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1; wherein (a) is the N2- adsorption-desorption isotherm, and (b) is the pore size distribution diagram;

[0020] Figure 5 This is the stress-strain curve of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1 during 10 cycles of compression;

[0021] Figure 6 This is a graph showing the adsorption performance of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1 at different adsorption times;

[0022] Figure 7 is an adsorption isotherm diagram of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1;

[0023] Figure 8 This is a diagram of the cyclic adsorption-desorption of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1;

[0024] Fig. 9 This is a graph showing the effect of competitive ions on the adsorption of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1;

[0025] Fig.10 This is a comparison chart of the adsorption performance of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1 and the hydrogel adsorbents prepared in Examples 2 to 5;

[0026] Fig.11This is a comparison chart of the adsorption performance of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1 and the hydrogel adsorbents prepared in Examples 5 and 6 and Comparative Experiments 1 and 2. DETAILED DESCRIPTION

[0027] Specific implementation method 1: This implementation method is a method for preparing a nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent, which is specifically carried out in the following steps:

[0028] 1. Stir the polybutadiene nano rubber latex and acrylamide in a colorimetric tube to obtain a mixed system; then irradiate with a dose of 2.5 kGy to 20 kGy. 60 Co-γ-ray irradiation for 0.5 h to 4 h, the product was fully swollen after washing to obtain polyacrylamide / nano rubber hydrogel PAM / PB;

[0029] 2. Soak the polyacrylamide / nano rubber hydrogel PAM / PB obtained in step 1 in a sodium hypochlorite solution, then wash to remove residual sodium hypochlorite, then soak in a sodium thiosulfate solution, then wash and dry to obtain an amino-substituted product hydrogel PAM / PB-NH2;

[0030] 3. Soaking the hydrogel PAM / PB-NH2 obtained in step 2 in a glutaraldehyde solution, then washing and drying to obtain an aldehyde-substituted product hydrogel PAM / PB-CHO;

[0031] 4. Soaking the hydrogel PAM / PB-CHO obtained in step 3 in a diaminomaleonitrile solution, then washing and drying to obtain DAMN and a grafted product hydrogel PAM / PB-DAMN;

[0032] 5. Dissolve hydroxylamine hydrochloride in a methanol / water mixed solution, adjust the pH, add the hydrogel PAM / PB-DAMN obtained in step 4 to obtain a reaction system, heat the reaction system for reaction, cool it to room temperature, wash and dry it, and obtain a nano-rubber toughened diamidoximine-based hydrogel uranium adsorbent PAM / PB-DAMN-AO.

[0033] The beneficial effects of this embodiment are:

[0034] In this embodiment, PB is uniformly dispersed in PAM by irradiation. PB, as a toughening and strengthening unit, has an improving effect on the mechanical properties of PAM. At the same time, after multi-step chemical soaking and grafting of DAMN groups and amidoximation reaction, a nano-rubber toughened bisamidoxime-based hydrogel uranium adsorbent is obtained. The presence of the bifunctional group improves the chelation effect on uranyl ions and significantly improves the adsorption performance.

[0035] Specific embodiment 2: This embodiment is different from the specific embodiment 1 in that the mass ratio of the polybutadiene nano rubber latex to acrylamide in step 1 is 1 g:(1.25-20) g. The rest is the same as the specific embodiment 1.

[0036] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the washing and swelling method described in step 1 is to use deionized water for treatment. The rest is the same as specific implementation method 1 or 2.

[0037] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the concentration of the sodium hypochlorite solution in step 2 is 0.08 mol / L to 0.24 mol / L, the volume ratio of polyacrylamide / nano rubber hydrogel PAM / PB to the sodium hypochlorite solution is 1 g: (100 to 200) mL, and the soaking time is 1 h to 3 h. Others are the same as specific embodiments 1 to 3.

[0038] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the concentration of the sodium thiosulfate solution in step 2 is 0.1 mol / L to 0.4 mol / L, the mass ratio of polyacrylamide / nano rubber hydrogel PAM / PB to the sodium thiosulfate solution is 1 g: (100 to 200) mL, and the soaking time is 2 h to 4 h. Others are the same as specific embodiments 1 to 4.

[0039] Specific implementation 6: This implementation is different from Specific implementations 1 to 5 in that the solvent of the glutaraldehyde solution in step 3 is anhydrous ethanol, the mass fraction of glutaraldehyde is 1% to 10%, and the soaking time is controlled to be 2 to 4 hours. Others are the same as Specific implementations 1 to 5.

[0040] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the solvent in the diaminomaleonitrile solution in step 4 is anhydrous ethanol, wherein the mass fraction of diaminomaleonitrile is 1% to 10%. The rest is the same as specific embodiments 1 to 6.

[0041] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: in the methanol / water mixed solution described in step five, the volume ratio of methanol to water is 1 mL: (0.5-1.5) mL, the mass ratio of hydroxylamine hydrochloride to the volume ratio of methanol / water mixed solution is 1 g: (10-30) mL, the mass ratio of hydroxylamine hydrochloride to hydrogel PAM / PB-DAMN is 1 g: (0.05-0.15) g, and the soaking time is 2 h to 4 h. Others are the same as specific embodiments one to seven.

[0042] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: in step 5, one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate and triethylamine are used to adjust the pH value to 6 to 8. The rest is the same as specific embodiments 1 to 8.

[0043] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the heating reaction temperature in step 5 is 60° C. to 80° C. and the reaction time is 4 h to 6 h. The rest is the same as specific embodiments 1 to 9.

[0044] The content of the present invention is not limited to the content of the above-mentioned embodiments. The combination of one or several specific embodiments can also achieve the purpose of the invention.

[0045] Embodiment 1:

[0046] The present embodiment provides a method for preparing a nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent, which is specifically carried out in the following steps:

[0047] 1. Stir 5g PB and 20g AM in a 25mL colorimetric tube to obtain a mixed system; then irradiate with a dose of 5kGy. 60 After Co-γ-ray irradiation for 1 h, the product was fully swollen after washing with deionized water to obtain polyacrylamide / nano rubber hydrogel PAM / PB;

[0048] 2. Soak 1 g of the polyacrylamide / nano rubber hydrogel PAM / PB obtained in step 1 in a 0.16 mol / L sodium hypochlorite solution for 1.5 h, then wash to remove residual sodium hypochlorite, and then soak in a 0.2 mol / L sodium thiosulfate solution for 3 h, then wash and dry to obtain an amino-substituted product hydrogel PAM / PB-NH2;

[0049] 3. Soak 1 g of the hydrogel PAM / PB-NH2 obtained in step 2 in a 2% by mass glutaraldehyde solution for 3 h, then wash and dry to obtain the aldehyde-substituted product hydrogel PAM / PB-CHO;

[0050] 4. Soak 1 g of the hydrogel PAM / PB-CHO obtained in step 3 in a 1% by mass DAMN solution for 3 h, then wash and dry to obtain a DAMN-grafted hydrogel PAM / PB-DAMN;

[0051] 5. Dissolve 8 g of hydroxylamine hydrochloride in a mixed solution of methanol / water (V:V=1:1), then adjust the pH to 7.5, add 1 g of the hydrogel PAM / PB-DAMN obtained in step 4, soak for 3 h to obtain a reaction system, heat the reaction system to 70 ° C for 5 h, then cool to room temperature and wash and dry to obtain a nano-rubber toughened diamidoximine-based hydrogel uranium adsorbent PAM / PB-DAMN-AO.

[0052] Figure 1 FT-IR image of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1, 1173 cm -1 The characteristic absorption peak of carbon-nitrogen bond (CN) is 932 cm -1 The characteristic absorption peak of nitrogen-oxygen bond (NO) is at , and the characteristic chemical bond of amine oxime group is generated, which proves that the amidoximation reaction is successful.

[0053] Figure 2 This is a SEM image of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1. The hydrogel has a network structure as a whole, with many holes and randomly distributed large and small holes. This structure provides channels for the entry of uranyl ions and provides favorable conditions for adsorption.

[0054] Figure 3 This is the XPS graph of the nano-rubber toughened bis-amidoxime-based hydrogel uranium adsorbent prepared in Example 1. The spectrum shows characteristic peaks of amino carbon CN (285.7 eV), oxime carbon C=N (285.1 eV), oxime nitrogen C=N (400.1 eV), amino nitrogen CN (399.6 eV) and oxime oxygen NO (532.6 eV) AO groups, further proving the success of the amidoximation reaction.

[0055] Figure 4 This is the BET diagram of the nano-rubber toughened diamidoximine-based hydrogel uranium adsorbent prepared in Example 1. The diagram shows a type IV isotherm with an H3-type hysteresis loop, indicating the presence of a mesoporous structure. The pore size distribution tested is mainly concentrated within 25 nm. The nanopores in the hydrogel are more conducive to the binding of uranyl ions, providing binding time at the adsorption site, thereby improving the uranium adsorption performance.

[0056] Figure 5 This is the stress-strain curve of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1 during 10 cycles of compression. After 10 cycles of compression tests, the stress value of the hydrogel is almost not lost, and the total strain value of the hydrogel can still reach 80%. The hydrogel has excellent mechanical properties.

[0057] Uranium adsorption test: 2.1092 g of UO2(NO3)2·6H2O was accurately weighed and dissolved in ultrapure water, then transferred to a 1L volumetric flask and fixed to volume to obtain a 1000 mg / L uranium solution. The uranium solutions of different concentration gradients used in subsequent performance test experiments were all diluted from a 1000 mg / L high-concentration uranium solution. The concentration of the uranium solution was quantitatively analyzed using a UV-visible spectrophotometer. Arsenazo(III) was used as a color developer to chelate with U(VI) and exhibit a characteristic absorption peak at a fixed wavelength of 652 nm. Within a certain concentration range, the concentration of U(VI) in the solution was linearly related to the absorbance measured by the UV-visible spectrophotometer.

[0058] Take 20 mL of uranium solution with a concentration of 100 mg / L, adjust the solution pH to 5.5 with 0.1 mol / L NaOH or HNO3 solution, add 12 mg of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1, and then oscillate in a constant temperature water bath at a temperature of 298 K. After adsorption for 24 hours, centrifuge to separate the supernatant, and use an ultraviolet spectrophotometer to measure and calculate the uranium ion concentration to obtain adsorption data.

[0059] Figure 6 The adsorption performance diagram of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1 at different adsorption times; the results show that the contact time between the adsorbent and the uranium solution is an important factor affecting the uranium adsorption performance. The kinetic curve is fitted, and the result is more consistent with the pseudo-second-order kinetic model. The adsorbent in Example 1 shows rapid adsorption efficiency, and the adsorption equilibrium is reached in 180 minutes.

[0060] Take 20 mL of uranium solutions with concentrations of 40 mg / L, 50 mg / L, 60 mg / L, 80 mg / L, 100 mg / L, 150 mg / L, 300 mg / L, 400 mg / L and 500 mg / L respectively, adjust the pH value to 5.5 with 0.1 mol / L NaOH or HNO3 solution, add 12 mg of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1, and then oscillate in a constant temperature water bath at a temperature of 298 K. After adsorption for 24 hours, centrifuge to separate the supernatant, and use an ultraviolet spectrophotometer to measure and calculate the uranium ion concentration to obtain adsorption data.

[0061] Figure 7 The adsorption isotherm of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1 is shown in Figure 1. The isotherm is fitted and the result is consistent with the Langumir isothermal adsorption model. The saturated adsorption capacity of the adsorbent in a 500 mg / L uranium solution is 289.6 mg / g. It has excellent adsorption performance.

[0062] Take 20 mL of uranium solution with a concentration of 100 mg / L, adjust the pH value to 5.5 with 0.1 mol / L NaOH or HNO3 solution, add 12 mg of the nano-rubber toughened diamidoximine-based hydrogel uranium adsorbent prepared in Example 1, and then oscillate in a constant temperature water bath at a temperature of 298 K. After adsorption for 24 hours, centrifuge to separate the supernatant, and use an ultraviolet spectrophotometer to measure and calculate the uranium ion concentration to obtain adsorption data; add the centrifugal product to 20 mL of desorbent NaHCO3 with a concentration of 0.1 mol / L, oscillate in a constant temperature water bath at a temperature of 298 K, desorb for 6 hours, and centrifuge to obtain the desorbed adsorbent.

[0063] Figure 8 This is the adsorption-desorption cycle diagram of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1. After four adsorption-desorption processes, the uranium removal rate is still 95.7%, and the adsorption amount can still reach 136.8 mg / g, which has excellent cyclic regeneration ability.

[0064] Select Ca 2+ , Cu 2+ , K + Mg 2+ 、Na + 、Ni 2+ 、Zn 2+ A salt solution is mixed with a uranium solution to obtain a mixed solution, wherein the initial concentration of each ion in the mixed solution is 100 mg / L, and the pH of the solution is adjusted to 5.5 with 0.1 mol / L NaOH or HNO3 solution. 20 mL of the above solution is transferred, 12 mg of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1 is added, and then the mixture is shaken in a constant temperature water bath at a temperature of 298 K. After adsorption for 24 hours, the supernatant is separated by centrifugation, and the concentrations of uranium and other cations in the solution are analyzed by inductively coupled plasma mass spectrometry (ICP-MS).

[0065] Fig. 9 This is a graph showing the effect of competitive ions on the adsorption of the nano rubber toughened diamidoximine-based hydrogel uranium adsorbent prepared in Example 1. As can be seen from the figure, under the coexistence of many ions, the material still has a relatively high adsorption capacity of 45.3 mg / g for uranium.

[0066] Embodiment 2: This embodiment is different from Embodiment 1 in that the irradiation dose in step 1 is 2.5 kGy. The rest is the same as Embodiment 1.

[0067] Embodiment 3: This embodiment is different from Embodiment 1 in that the irradiation dose in step 1 is 10 kGy. The rest is the same as Embodiment 1.

[0068] Embodiment 4: This embodiment is different from Embodiment 1 in that the irradiation dose in step 1 is 15 kGy. The rest is the same as Embodiment 1.

[0069] Example 5: This comparative experiment is different from Example 1 in that 2.5 g PB is mixed with 22.5 g AM in step 1. The rest is the same as Example 1.

[0070] Example 6: This comparative experiment is different from Example 1 in that 10 g PB and 15 g AM are mixed in step 1. The rest is the same as Example 1.

[0071] Comparative Experiment 1: This comparative experiment is different from Example 1 in that 15 g PB and 10 g AM are mixed in step 1. The rest is the same as Example 1.

[0072] Comparative Experiment 2: This comparative experiment is different from Example 1 in that 20 g PB and 5 g AM are mixed in step 1. The rest is the same as Example 1.

[0073] Take 20 mL of uranium solution with a concentration of 100 mg / L, adjust the solution pH to 5.5 with 0.1 mol / L NaOH or HNO3 solution, add 12 mg of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Examples 1 to 4, and then oscillate in a constant temperature water bath at a temperature of 298 K. After adsorption for 24 hours, centrifuge to separate the supernatant, and use an ultraviolet spectrophotometer to measure and calculate the uranium ion concentration to obtain adsorption data. Fig.10 This is a comparison chart of the adsorption performance of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1 and the hydrogel adsorbents prepared in Examples 2 to 4.

[0074] Take 20 mL of uranium solution with a concentration of 100 mg / L, adjust the solution pH to 5.5 with 0.1 mol / L NaOH or HNO3 solution, add 12 mg of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1 and Example 5 to Example 6, and then oscillate in a constant temperature water bath at a temperature of 298 K. After adsorption for 24 hours, centrifuge to separate the supernatant, and use an ultraviolet spectrophotometer to measure and calculate the uranium ion concentration to obtain adsorption data. Fig.11 This is a comparison chart of the adsorption performance of the nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent prepared in Example 1 and the hydrogel adsorbents prepared in Examples 5 and 6 and Comparative Experiments 1 and 2.

Claims

1. A method for preparing a nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent, characterized in that The method is specifically carried out in the following steps:

1. Stir the polybutadiene nano rubber latex and acrylamide in a colorimetric tube to obtain a mixed system; then irradiate with a dose of 2.5 kGy to 20 kGy. 60 Co-γ-ray irradiation for 0.5 h to 4 h, the product was fully swollen after washing to obtain polyacrylamide / nano rubber hydrogel PAM / PB; 2. Soak the polyacrylamide / nano rubber hydrogel PAM / PB obtained in step 1 in a sodium hypochlorite solution, then wash to remove residual sodium hypochlorite, then soak in a sodium thiosulfate solution, then wash and dry to obtain an amino-substituted product hydrogel PAM / PB-NH2; 3. Soaking the hydrogel PAM / PB-NH2 obtained in step 2 in a glutaraldehyde solution, then washing and drying to obtain an aldehyde-substituted product hydrogel PAM / PB-CHO; 4. Soaking the hydrogel PAM / PB-CHO obtained in step 3 in a diaminomaleonitrile solution, then washing and drying to obtain DAMN and a grafted product hydrogel PAM / PB-DAMN; 5. Dissolve hydroxylamine hydrochloride in a methanol / water mixed solution, adjust the pH, add the hydrogel PAM / PB-DAMN obtained in step 4 to obtain a reaction system, heat the reaction system for reaction, cool it to room temperature, wash and dry it, and obtain a nano-rubber toughened diamidoximine-based hydrogel uranium adsorbent PAM / PB-DAMN-AO.

2. The method for preparing a nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent according to claim 1, characterized in that The mass ratio of the polybutadiene nano rubber latex to acrylamide in step 1 is 1 g:(1.25-20) g.

3. The method for preparing a nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent according to claim 1, characterized in that The washing and swelling method described in step 1 is to treat with deionized water.

4. The method for preparing a nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent according to claim 1, characterized in that The concentration of the sodium hypochlorite solution described in step 2 is 0.08 mol / L to 0.24 mol / L, the volume ratio of polyacrylamide / nano rubber hydrogel PAM / PB to the sodium hypochlorite solution is 1 g: (100 to 200) mL, and the immersion time is 1 h to 3 h.

5. The method for preparing a nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent according to claim 1, characterized in that The concentration of the sodium thiosulfate solution described in step 2 is 0.1 mol / L to 0.4 mol / L, the mass ratio of polyacrylamide / nano rubber hydrogel PAM / PB to the sodium thiosulfate solution is 1 g: (100 to 200) mL, and the soaking time is 2 h to 4 h.

6. The method for preparing a nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent according to claim 1, characterized in that The solvent of the glutaraldehyde solution in step 3 is anhydrous ethanol, wherein the mass fraction of glutaraldehyde is 1% to 10%, and the immersion time is controlled to be 2 to 4 hours.

7. The method for preparing a nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent according to claim 1, characterized in that The solvent in the diaminomaleonitrile solution in step 4 is anhydrous ethanol, wherein the mass fraction of diaminomaleonitrile is 1% to 10%.

8. The method for preparing a nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent according to claim 1, characterized in that In the methanol / water mixed solution described in step five, the volume ratio of methanol to water is 1 mL: (0.5-1.5) mL, the mass ratio of hydroxylamine hydrochloride to the volume ratio of the methanol / water mixed solution is 1 g: (10-30) mL, the mass ratio of hydroxylamine hydrochloride to the hydrogel PAM / PB-DAMN is 1 g: (0.05-0.15) g, and the immersion time is 2 h to 4 h.

9. The method for preparing a nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent according to claim 1, characterized in that Step 5: Use one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate and triethylamine to adjust the pH value to 6-8.

10. The method for preparing a nano-rubber toughened bisamidoximine-based hydrogel uranium adsorbent according to claim 1, characterized in that In step 5, the heating reaction temperature is 60°C to 80°C, and the reaction time is 4h to 6h.